Prevalence of and Barriers to Dual-Contraceptive Methods Use among Married Men and Women Living with HIV in India - Venkatesan Chakrapani; Trace Kershaw; Murali Shunmugam; Peter A. Newman; Deborah H. Cornman; Robert Dubrow (Hindawi Limited, 2011)
Objective. To describe the prevalence and correlates of dual-contraceptive methods use (condoms and an effective pregnancy prevention method) and barriers to their use among married persons living with HIV (PLHIV) in India. Methods. We conducted a quantitative survey (93 men, 97 women), 25 in-depth interviews, seven focus groups, and five key informant interviews. Results. Prevalence of dual- contraceptive method use increased from 5% before HIV diagnosis to 23% after diagnosis (P < 0.001). Condoms were the most common contraceptive method, with prevalence increasing from 13% before diagnosis to 92% after diagnosis (P < 0.001). Barriers to using noncondom contraceptives were lack of discussion about noncondom contraceptives by health care providers, lack of acceptability of noncondom contraceptives among PLHIV, and lack of involvement of husbands in family planning counseling. Conclusion. There is a need for interventions, including training of health care providers, to increase dual-contraceptive methods use among married PLHIV.